CHANGE MANAGEMENT: CONCEPT, APPLICATION, AND ITS RELEVANCE FOR HIGHER EDUCATION MANAGEMENT - Iskandar Iskandar (Journal Of Educational Experts (JEE), 2019)
Change is a necessity. Implementation of change management is a must for the organization, if it wants to survive and develop forward. However, in fact, not all heads of organizations are aware of and understand the importance of it. This paper explores what this concept actually is. How is the application, especially when it is associated to the contemporary demands facedby the organization.Then, how far its relevance for management at the level of praxis, especially college management. This paper has not become a comprehensive text that addresses the above theme, but rather as ‘a trigger’ that hopefully can stimulate serious discussions among the academic community in order to obtain a clearer, more coherent, and more complete picture.